2015
DOI: 10.1093/toxsci/kfv193
|View full text |Cite
|
Sign up to set email alerts
|

The AhR and NF-κB/Rel Proteins Mediate the Inhibitory Effect of 2,3,7,8-Tetrachlorodibenzo-p-Dioxin on the 3′ Immunoglobulin Heavy Chain Regulatory Region

Abstract: Transcriptional regulation of the murine immunoglobulin (Ig) heavy chain gene (Igh) involves several regulatory elements including the 3'Igh regulatory region (3'IghRR), which is composed of at least 4 enhancers (hs3A, hs1.2, hs3B, and hs4). The hs1.2 and hs4 enhancers exhibit the greatest transcriptional activity and contain binding sites for several transcription factors including nuclear factor kappaB/Rel (NF-κB/Rel) proteins and the aryl hydrocarbon receptor (AhR). Interestingly, the environmental immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
(104 reference statements)
1
15
0
Order By: Relevance
“…This is a common feature of nuclear receptors, and contributes to modifications to cellular events downstream of their engagement 73 , 74 . For example, the AHR has been shown to interact with subunits of the nuclear factor kappa b (NF-κB) complex in myeloid cells, B cells, and fibroblasts 75 77 , although the precise NF-κB family members with which AHR interacts varied among cell types. Thus, interactions with cofactors are likely cell-type specific, which may help to explain some of the cell-type specific effects observed among the AHR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…This is a common feature of nuclear receptors, and contributes to modifications to cellular events downstream of their engagement 73 , 74 . For example, the AHR has been shown to interact with subunits of the nuclear factor kappa b (NF-κB) complex in myeloid cells, B cells, and fibroblasts 75 77 , although the precise NF-κB family members with which AHR interacts varied among cell types. Thus, interactions with cofactors are likely cell-type specific, which may help to explain some of the cell-type specific effects observed among the AHR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…These changes were not due to alterations in viral replication, as the viral load was unchanged by AhR activation or inhibition. The mechanism driving cytokine changes during MHV infection is likely complex but probably involves interaction of activated AhR with NF-B (30,(33)(34)(35)55) (Fig. 1).…”
Section: Mhv-a59 Infection Induces Tiparp Expression Through Ifn-i-dementioning
confidence: 99%
“…AhR activation by chemical agonists has been shown to influence the differentiation (24)(25)(26)(27)(28) and cytokine/chemokine production (25,26,(29)(30)(31)(32) of T cells, dendritic cells, and macrophages. AhR has also been shown to bind to and modulate the transcription specificity of NF-B in multiple experimental settings, which could contribute to cytokine modulation (30,(33)(34)(35). Other studies have shown that AhR activation in immune cells is driven by IDO1, and the resulting IDO1-AhR-IDO1 positivefeedback loop helps to establish immunotolerance (18,36,37).…”
mentioning
confidence: 99%
“…[48][49][50] Furthermore, a recent paper has shown that upon TCDD treatment altered expression of NFKB/REL members may, along with AHR activation, mediate a decrease in Ig expression. 51 As such, increased PAI2 expression may provide protection to less-sensitive strains via regulation of NFKB/REL signaling. Human PAI2 has also been reported to bind and protect retinoblastoma protein (RB1) from calpain cleavage ultimately leading to increase RB1 levels within the cell leading to increased cell survival.…”
Section: Discussionmentioning
confidence: 99%